2017
DOI: 10.3748/wjg.v23.i22.4090
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease incidence in Czech children: A regional prospective study, 2000-2015

Abstract: AIMTo examine the incidence and trends in pediatric inflammatory bowel diseases (IBDs) over 2000-2015 and project the incidence to 2018.METHODSA 16-year prospective study of IBD patients < 19 years of age was conducted in the Czech Republic (the Pilsen region). All incident IBD cases within a well-defined geographical area were retrieved from a prospectively collected computerized clinical database. Historical Czech data were used for comparison (1990-2001). Our catchment population was determined from the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
9
1
Order By: Relevance
“…Kolek et al[ 140 ] published results from Moravia (the eastern part of the Czech Republic) showing increasing incidence of CD and UC between 1999 and 2001. The Czech Republic has among the highest rates of IBD worldwide as recently observed by our group (2000-2015)[ 45 ] (10.0, 6.2, 2.8 and 1.0/100000 for IBD, CD, UC and IBD-U, respectively) and have been shown to be increasing in future projections[ 45 ]. In neighboring Poland, UC incidence was higher than that of CD with significant regional differences, but the incidence was markedly lower than that observed in the West.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Kolek et al[ 140 ] published results from Moravia (the eastern part of the Czech Republic) showing increasing incidence of CD and UC between 1999 and 2001. The Czech Republic has among the highest rates of IBD worldwide as recently observed by our group (2000-2015)[ 45 ] (10.0, 6.2, 2.8 and 1.0/100000 for IBD, CD, UC and IBD-U, respectively) and have been shown to be increasing in future projections[ 45 ]. In neighboring Poland, UC incidence was higher than that of CD with significant regional differences, but the incidence was markedly lower than that observed in the West.…”
Section: Discussionmentioning
confidence: 74%
“…Few studies using north-south/west-east gradients have demonstrated particularly high rates in the north[ 39 - 42 ], except for northern France[ 43 ] and Spain[ 44 ]. Although our review did not specifically investigate disease incidence gradients, this phenomenon has been less prominent over the last three decades[ 45 - 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polish incidence is 2.7/100 000 children/year, and in the Czech Republic it is as many as 10/100 000 children/year. 33,34 Polish authors, as a possible reason for the unexpectedly low incidence cite the possibility of underreporting of patients due to differences in diagnostic treatment options in different parts of the country. 34 Also, when comparing data from those 2 countries, it should be borne in mind that the Polish study was done more than 10 years before the Czech and the incidence is rising all over the world.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Polish authors, as a possible reason for the unexpectedly low incidence cite the possibility of underreporting of patients due to differences in diagnostic treatment options in different parts of the country. 34 Also, when comparing data from those 2 countries, it should be borne in mind that the Polish study was done more than 10 years before the Czech and the incidence is rising all over the world. PIBD incidence in Germany is estimated to be between 5 and 11/100 000 children/year 35 and in Netherlands it is 5.2/100 000 children/year, 29 and both are lower than ours.…”
Section: Discussionmentioning
confidence: 99%
“…Like that of Johne’s disease, the incidence of Crohn’s disease continues to increase with consequential economic health costs [25,26,27,28,29], particularly in children. Both Northern and Central Europe and Australia showed an average 5-fold per decade increase in the disease in children under 16 [30,31,32].…”
Section: Introductionmentioning
confidence: 99%